A Numerical Evaluation of a Cover Embankment Model on Very Soft Halic Dredge Material - Terzi, N. Ugur; Selcuk, M. Ergenekon; Sengul, T. (IOS PRESS, 2011)
The objective of this study is to evaluate the consolidation process and long-term deformation behavior of an embankment constructed on dredge material from the Halic (know as Golden Horn) in Istanbul. A comprehensive laboratory studies were performed on dredge material and with using the laboratory test results, finite element numerical method was carried out to analyze the embankment construction procedure, and its relationship with the Halic dredge materials. The Soft Soil Creep Model for very soft dredge material and the Mohr-Coulomb Soil Model for embankment material was utilized in the numerical investigations. For the numerical analysis, engineering and consolidation characteristics of the Halic dredge material were determined by using in-situ and laboratory tests. The results proved that the chosen Soft Soil Model and Mohr-Coulomb for the Halic dredge and embankment materials are efficient in assessing the geotechnical behavior and the long term pore water pressure dissipation of the embankment-foundation system model.
Keywords: Halic dredge material; staged construction; pore pressure dissipation; soft soil model; Engineering